DIGITALISASI KOLEKSI LANGKA DI UPT. PERPUSTAKAAN UNIVERSITAS GADJAH MADA - Srikana, Ni Putu Winda Rahayu; Ginting, Richard Togaranta; Haryanti, Ni Putu Premierita (Jurnal Ilmiah Ilmu Perpustakaan dan Informasi, 2023)
Technological improvements have made library collections also make efforts to preserve collections by digitizing them. Collection digitization is an effort to preserve information in the library. Digitization is carried out based on consideration of the type and criteria of the collection, such as collections that are no longer published or are rare. The purpose of this study is to determine the process of digitization at UPT. Gadjah Mada Library.  This research is a descriptive research with a qualitative approach. Selected informants know the data related to research in accordance with the principles, considerations and criteria of purposive sampling technique. Data collection techniques also use observation, interviews, documentation and literature study. The results of this study indicate that the UPT. The Gadjah Mada University Library preserves rare collections by digitizing them. Digitization was carried out on as many as 33 thousand rare collections, and 2505 of these collections have been uploaded on the rare collections page. Annually 300 book titles have been successfully digitized. The digitization process uses different tools according to the level of fragility with the flow of capturing images, editing, and uploading 10 pages per book title. This digitization is able to answer the problem of preserving collections so that it is useful for the academic community to the general public who wish to gain knowledge related to rare collections.